Efficiency in Household Decision-Making: Evidence from the Retirement Savings of US Couples - Choukhmane, Taha; Goodman, Lucas; O’Dea, Cormac (American Economic Review, 2025)
We study how couples allocate retirement-saving contributions across each spouse’s account. In a new dataset covering over a million US individuals, we find retirement contributions are not allocated to the account with the highest employer match rate. This lack of coordination—which goes against the assumptions of most models of household decision-making—is common, costly, persistent over time, and cannot be explained by inertia, auto-enrollment, or simple heuristics. Complementing the administrative evidence with an online survey, we find that inefficient allocations reflect both financial mistakes as well as deliberate choices, especially when trust and commitment inside the households are weak. (JEL D13, G51, J26, J32)